Pengaruh Akuntabilitas dan Sistem Pengendalian Internal terhadap Kinerja Pemerintah Daerah - Flora Evita; Dian Fitria Handayani (Jurnal Eksplorasi Akuntansi, 2024)
The objective of this research was to explore the impact of both accountability and internal control systems on the performance of the local government within Pasaman District. The study encompassed a population of 38 OPD in Pasaman District. The study's participants consisted of OPD heads, treasurers, finance heads, and SPI heads. Employing primary data collected through questionnaires, the research involved 152 direct respondents. The findings of the research indicate that:1) Accountability yields a favorable influence on the performance of the local government in Pasaman District. 2) The internal control system also demonstrates a positive impact on the local government's performance within Pasaman District. The combined contribution of the independent variables in explaining the dependent variable amounts to 8.5%, leaving the remaining 81.5% to be explained by external factors not covered in this research. To enhance future research, it is recommended to introduce additional variables that are relevant to local government performance. Moreover, increasing the respondent pool and expanding the research scope can enhance generalizability.